Multidisciplinary context of research of a new drug in infectious and inflammatory diseases - Shapovalov, Valentyn; Shapovalova, Viktoriia; Osyntseva, Alina; Shapovalov, Valerii; Veits, Oleksandr; Titarenko, Yurii (Annals of Mechnikov's Institute, 2024)
Introduction. The multidisciplinary context of the study of a new drug for infectious-inflammatory diseases based on the combination of evidence-selected pharmacological substances paracetamol and ascorbic acid was developed. Competences of the organization of pharmacy, medicine, pharmacology, forensic pharmacy, pharmaceutical analysis, and social medicine were used. The aim: Noted that the raw material base, production in the conditions of pharmacies and pharmaceutical enterprises of paracetamol + ascorbic acid tablets is economically expedient, socially oriented in the conditions of a military conflict. Materials and methods. Quality control methods have been developed: determination of para-aminophenol, paracetamol, and ascorbic acid. The results of organizational, documentary, pharmacological, medical, pharmaceutical, physicochemical, and social studies were used. According to physical and chemical studies, the determination of para-aminophenol by spectrophotometric method is proposed. It was determined that experimental samples of the drug do not contain impurities of free para-aminophenol. The maximum permissible content of para-aminophenol in tablets of the drug under study is no more than 0.1%. Results. The complex of developed methods and standardization of quality control indicators of paracetamol + ascorbic acid tablets meet the requirements of the latest pharmacopoeias. The methods of quantitative determination of the active substances of the drug used in the development of analytical and control documentation, the system of quality control of the drug in further production in the conditions of pharmacies or pharmaceutical enterprises. Conclusions. The main areas of application of paracetamol + ascorbic acid tablets are indicated: infectious diseases with an increase in temperature; pain syndromes of weak and medium intensity of various genesis. Appeared promising to include the new drug in the pharmacotherapy schemes of health care institutions. The social context of the study is relevant in emergency situations, in the conditions of a military conflict, to reduce the suffering of victims of pain, inflammation, fever, and improve the quality of life of patient Keywords: paracetamol ascorbic acid analysis application